2019
DOI: 10.1101/583492
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Modular actin nano-architecture enables podosome protrusion and mechanosensing

Abstract: Basement membrane transmigration during embryonal development, tissue homeostasis and tumor invasion relies on invadosomes, a collective term for invadopodia and podosomes. An adequate structural framework for this process is still missing. Here, we reveal the modular actin nano-architecture that enables podosome protrusion and mechanosensing. The podosome protrusive core contains a central branched actin module encased by a linear actin module, each harboring specific actin interactors and actin isoforms. Fro… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 70 publications
2
18
1
Order By: Relevance
“…In this model, stochastic Arp2/3 activation produces actin foci by local bursts of branching of preexisting short filaments. Branched actin polymerization may either push on the membrane to generate protrusions, similarly as it happens in podosomes (van den Dries et al, 2019), or synergize with BCR-dependent signaling and endocytic proteins to produce an invagination of the plasma membrane and extract the antigen. Formin-generated filaments may stabilize the foci by surrounding and connecting them, which, along with crosslinking and tensioning by myosin IIa, could help to direct the foci-generated forces perpendicularly to the plasma membrane.…”
Section: Discussionmentioning
confidence: 99%
“…In this model, stochastic Arp2/3 activation produces actin foci by local bursts of branching of preexisting short filaments. Branched actin polymerization may either push on the membrane to generate protrusions, similarly as it happens in podosomes (van den Dries et al, 2019), or synergize with BCR-dependent signaling and endocytic proteins to produce an invagination of the plasma membrane and extract the antigen. Formin-generated filaments may stabilize the foci by surrounding and connecting them, which, along with crosslinking and tensioning by myosin IIa, could help to direct the foci-generated forces perpendicularly to the plasma membrane.…”
Section: Discussionmentioning
confidence: 99%
“…Super-resolution microscopy analysis of the podosome architecture shows that both vinculin and myosin II are linked to actin filaments in the podosomal ring and that these proteins and their associated actin filaments form two separate modules surrounding the actin core. [55] This organization of integrins, mechanosensitive proteins, actin, and myosin in podosomes thus differs from FAs, in which talin/vinculin directly connect integrins to actomyosin cytoskeleton. Invadosomes can form under low cellular tension, since they are driven by actin polymerization, and might act as mechanosensors by integrins that pull on the ECM adjacent to the protrusive actin core.…”
Section: Mechanosensory Function Of Podosomes/invadopodiamentioning
confidence: 99%
“…The to produce protrusive forces. 29,30,32 To investigate the role of the myosin II-enriched network, we used mice in which the Myh9 gene was specifically inactivated in the MK lineage (Myh9 -/mice). We previously reported that these mice are thrombocytopenic (336 × 10 9…”
Section: A Myosin Iia Enriched Network Is Required For the Collectimentioning
confidence: 99%